A life-changing event: patients' personal experiences of living with a long-term tracheostomy. Issue 2 (3rd July 2017) - Wrapson, Jill; Patterson, Niamh; Nakarada-Kordic, Ivana; Reay, Stephen
ABSTRACT: A tracheostomy is a commonly performed surgical procedure to alleviate some form of inadequate breathing. Tracheostomies may be temporary in the case of airway emergencies or may be for long-term access to airway and breathing depending on a patient's condition; in the case of the latter, this may have a major impact on a patient's life, one for which they are frequently unprepared. There is growing recognition that patients' views of their health care experience are an important component of quality of care. Through a deeper understanding of the challenges inherent in being a tracheostomy user, we sought via a two-stage study to inform the design of products for use by individuals with permanent tracheostomies. Stage one involved 10 participants taking part in in-depth interviews to understand the lived experience of long-term tracheostomy patients. Using thematic analysis, we found participants accepted the need for a tracheostomy but were keen to return to a life pre-tracheostomy. The restrictions the current designs of tracheostomy imposed was evidenced by the time required to spend on the daily care of their stoma and tracheostomy equipment, and by the significant restrictions on activities of daily living. Findings from stage one informed subsequent co-design workshops.